Water mites of the genus Atractides Koch, 1837 (Acari: Hydrachnidia: Hygrobatidae) from Ghana - Pešić, Vladimir; Smit, Harry (Zootaxa, 2015)
New records of water mites of the genus Atractides Koch, 1837 (Acari: Hydrachnidia: Hygrobatidae) from streams in Ghana are presented. Six species are reported, one of these, Atractides (Atractides) ghanaensis n. sp., is described as new for science. First records for Ghana are given for A. (Atractides) damkoehleri (K. Viets, 1916), A. (A.) latisetus (K. Viets, 1916), A. (Polymegapus) kuehnei (K. Viets, 1911) and A. (Tympanomegapus) tuberipalpis (K. Viets, 1913).